Endoscopic microvascular decompression without the use of rigid head fixation. (December 2022) - Blue, Rachel; Alexis, Maya; Mensah-Brown, Kobina; Yang, Andrew I.; Spadola, Michael; Ajmera, Sonia; Lee, John Y.K.
Highlights: Pinless head fixation is a reasonable option for select patients undergoing microvascular decompression. Surgical complications and operative times are similar between patients undergoing rigid head fixation and pinless head fixation. Communication with the anesthetics team to ensure no patient movement is essential when using pinless head fixation. Abstract: Background: Rigid fixation using a three-point skull clamp is a common practice during cranial surgery. Despite its frequency of use, rigid fixation is not without risk of complications including hemodynamic changes, skull fractures and venous thromboembolism. Given this, alternative head fixation should be considered when clinically appropriate. Objective: We sought to demonstrate a safe and effective "pinless" head fixation system during endoscopic microvascular decompression (E-MVD). Methods: Patients undergoing E-MVD were placed in the lateral position with a doughnut pillow under the head, providing support and reducing lateral neck flexion. The vertex of the cranium was angled 10 degrees downward and tape placed circumferentially in an X-shaped fashion around the head, avoiding direct pressure on the ears or eyes. The ipsilateral shoulder was pulled caudally away from the operative field and taped in place to ensure a maximal working corridor. Results: Fifty-two patients underwent the E-MVD procedure with pinless head fixation without any clinical complications. Indications included trigeminal neuralgia type 1 (63.5%), trigeminal neuralgia type 2 (5.8%), hemifacial spasm (19.2%), geniculate neuralgia (7.7%) and glossopharyngeal neuralgia (3.8%). There were no intraoperative or post operative complications and operative time for patients with three-point skull clamp fixation were similar compared to pinless head fixation. Conclusions: Pinless head fixation is a suitable alternative for certain patients undergoing E-MVD and provides a way to minimize complications that can occur secondary to rigid fixation. If pinless fixation is used, diligent and continued communication with the anesthetist is necessary to ensure there is no intraoperative patient movement.